2021
DOI: 10.21831/cp.v40i2.37155
|View full text |Cite
|
Sign up to set email alerts
|

Academic Stress and Coping Strategy in Relation to Academic Achievement

Abstract: Stress on students is more common and varied. Therefore, a good coping strategy is needed in order to control stress and increase academic achievement. The purposes of this study are: 1) to describe the level of academic stress and coping strategy; 2) to investigate the effect of the differences of gender, age, marital status, years of study and degrees on academic stress and coping; and 3) to analyze the relationship between academic stress, coping and academic achievement. This research used a quantitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 28 publications
4
21
5
1
Order By: Relevance
“…Academic stress is a psychological aspect that currently often appears during learning process in the COVID-19 era (Mahapatra, 2021;Chandra, 2021;Clabaugh, Duque & Logan, 2021;Fuente et al, 2021;Basheti, Mhaidat & Mhaidat, 2021). Academic stress is a condition in which a student experiences a mental disorder or pressure caused by learning activities at school (Basith, Syahputra, Fitriyadi, Rosmaiyadi, Fitri & Triani, 2021). A student who experienced high stress might have feelings of fear, anxiety, panic and worse can lead to weakness, nausea, dizziness, shaking, loss of concentration, and decreased motor skills (Runswick, Roca, Williams, Bezodis & North, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Academic stress is a psychological aspect that currently often appears during learning process in the COVID-19 era (Mahapatra, 2021;Chandra, 2021;Clabaugh, Duque & Logan, 2021;Fuente et al, 2021;Basheti, Mhaidat & Mhaidat, 2021). Academic stress is a condition in which a student experiences a mental disorder or pressure caused by learning activities at school (Basith, Syahputra, Fitriyadi, Rosmaiyadi, Fitri & Triani, 2021). A student who experienced high stress might have feelings of fear, anxiety, panic and worse can lead to weakness, nausea, dizziness, shaking, loss of concentration, and decreased motor skills (Runswick, Roca, Williams, Bezodis & North, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another factor is students are afraid of being infected by COVID-19, students must undergo isolation/lock down (Sundarasen et al, 2020), or the difficulty of carrying out physical education lessons online (Jumareng, Setiawan, Patah, Aryani, Asmuddin & Gani, 2021). Thus, these factors will trigger the low academic achievement of students (Basith, Syahputra, Fitriyadi, Rosmaiyadi, Fitri & Triani, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of students' deficient academic performance is complex and multivarious as it may arise from both academic and non-academic factors. However, it is indicated that one of the major influential factors is the students' academic stress [4,5,6]. Students may not all experience the academic stress with the same IOC intensity, therefore, it may cause different consequence from students to students.…”
Section: Introductionmentioning
confidence: 99%
“…The students' academic stress during the ICT program is concerning. It may not only jeopardize the students' academic performance and achievement, but also affect the students' confidence when latter dealing with projects or works at the international level [6]. Therefore, many have proposed various methods to cope with the ICT students' academic stress [1,18,19].…”
Section: Introductionmentioning
confidence: 99%